The Potential Hospital Strategic Planning in the COVID-19 ‎Era: A Systematic Review (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2022)
The COVID-19 pandemic has had a negative impact on hospitals. Hospitals have to survive and make various modifications in an effort to adapt to uncertain conditions, even transform the hospital's strategic plan that has been made previously. This study aims to re-evaluate various hospital strategic plans and evaluate aspects that often change during a pandemic, as well as determine the potential for strategic planning that can be used. We initially conducted an English literature search using the electronic database, PROQUEST, Scopus, Pubmed, Science Direct, 2020-2021. After that, the study quality assessment and data extraction were carried out. A total of 1951 eligible articles were identified, The remaining 18 studies were screened. Subsequently, 10 articles were removed after a full-text review. Finally, 8 articles met the inclusion criteria for this review. Most of the hospitals in the sample show increasing and decreasing returns to scale. The inefficiency stems from the hospital's suboptimal scale, not from a lack of management ability to convert inputs into outputs. Public health centers develop systems for office support, infection control, hospital coordination, and outsourced inventory control. The impact of COVID-19 that can be felt by the community in the field of health services is the lack of availability of hospitals that can accommodate COVID-19 patients and non-COVID-19 patients. There are still many hospitals that still accept non-COVID-19 patients who have comorbidities, while hospitals also accept COVID-19 patients, one of which is asymptomatic people (OTG) who are difficult to detect. Efforts to respond to the pandemic from the start and then implement strategic measures are highly dependent on the resilience of hospitals. Strategic planning transformation can be a solution for hospital organizations to remain resilient and advanced in an uncertain era.